2005
DOI: 10.1107/s1744309105007815
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray crystallographic analysis of a conserved domain in plants and prokaryotes fromPyrococcus horikoshiiOT3

Abstract: A plant-and prokaryote-conserved domain (PPC) has previously been found in AT-hook motif nuclear localized protein 1 (AHL1) localized in the nuclear matrix of Arabidopsis thaliana (AtAHL1). AtAHL1 has a DNA-binding function. Mutation analyses of AtAHL1 has previously revealed that the hydrophobic region of the PPC domain is essential for its nuclear localization. In this study, the PPC of the hyperthermophilic archaebacterium Pyrococcus horikoshii (PhPPC) was crystallized using the hanging-drop vapour-diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…8). The predicted tertiary structure of the PPC/DUF296 domain of SOB3/AHL29 suggests trimeric oligomerization, which is similar to that observed in seven determined crystal structures of this domain from Bacteria and Archaea [Protein Data Bank (PDB) ID: 2H6L, 2DT4, 2HX0, 2NMU, 2P6Y, 3HTN, and 3HWU] (14,15). Trimer formation in a proposed AHL complex is also supported by the physical interactions observed among AHLs in this study (Figs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…8). The predicted tertiary structure of the PPC/DUF296 domain of SOB3/AHL29 suggests trimeric oligomerization, which is similar to that observed in seven determined crystal structures of this domain from Bacteria and Archaea [Protein Data Bank (PDB) ID: 2H6L, 2DT4, 2HX0, 2NMU, 2P6Y, 3HTN, and 3HWU] (14,15). Trimer formation in a proposed AHL complex is also supported by the physical interactions observed among AHLs in this study (Figs.…”
Section: Discussionsupporting
confidence: 84%
“…Crystal structures of several bacterial and archaeal PPC/DUF296 proteins have been determined (14,15). All of the above prokaryotic PPC/DUF296 proteins share the same tertiary structure with five β-strands forming an antiparallel β-sheet, which partially surrounds a single α-helix.…”
mentioning
confidence: 99%
“…Methods and the material for sample preparation, crystallization, and preliminary crystallographic analysis of Ph PPC have been reported 3. X‐ray diffraction data of native and Se‐Met‐substituted crystals were collected to a resolution of 1.6 and 2.6 Å, respectively, at BL41XU in SPring‐8 (Hyogo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The second functional unit of the AHL proteins is the PPC domain, which is approximately 120 amino acids in length and exists as a single protein in Bacteria and Archaea [ 32 ]. Crystal structures of several bacterial and archaeal PPC proteins suggested that the prokaryotic PPC proteins form a trimer [ 36 , 37 ]. In land plants, the PPC domain has been identified in AHL proteins where it is located at the carboxyl end relative to the AT-hook motif(s) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%